Risk factors of rehospitalization in psychiatric inpatients within one year after discharge - Li Xinjie; He Hongbo; Zhang Jie (Sichuan jingshen weisheng, 2021)
ObjectiveTo explore the risk factors of rehospitalization of psychiatric inpatients within one year after discharge， so as to provide references for clinical evaluation and intervention.MethodsData of patients hospitalized in the Brain Hospital Affiliated to Guangzhou Medical University from 2013 to 2017 was collected through the electronic medical record system. Survival analysis was carried out to screen the risk factors for patient readmission. Cox risk regression and survival curve analysis were also performed， meantime， multiple linear regression was used to analyze the influencing factors of the time intervals between hospital discharge and subsequent readmission within one year.ResultsAmong the 22 807 hospitalized patients， 4 602 cases （20.2%） were readmitted within one year after discharge. Age， payment methods， disease diagnosis， number of hospitalizations and hospitalization days were risk factors for readmission （P<0.01）. The readmission rates of patients aged 21~30， 31~40， 41~50 and 51~60 were 0.706， 0.631， 0.610 and 0.693 times higher than those aged ≤20， respectively. The probability of readmission of patients with twice， three times and four times of hospitalization before was 3.015， 2.824 and 4.271 times higher than those with one time of hospitalization， respectively. The readmission rate of patients hospitalized for 21~40 days and above 101 days were 1.142 and 1.181 times higher than those hospitalized for less than 20 days， respectively. Age， hospitalization days and number of hospitalizations were the influencing factors of readmission within one year after discharge， and patients with older age had longer intervals between discharge and subsequent readmission （B=0.017， P<0.01）. The time intervals between discharge and subsequent readmission were significantly longer among patients who had been hospitalized for 61~80 days than among patients who had been hospitalized for less than 20 days （B=1.226， P<0.01）. Compared with patients with one time of hospitalization， the time intervals was significantly shorter among patients with twice of hospitalization （B=-1.386， P<0.01）.ConclusionPatients aged below 20 years old and those with two， four or more times of hospitalization before have a high rate of readmission within one year after discharge， and the readmission time may be earlier among patients with two times of hospitalization， and relatively later among patients who had been hospitalized for 61~80 days.